2020
DOI: 10.1093/geront/gnaa208
|View full text |Cite
|
Sign up to set email alerts
|

Within-Person Associations Among Self-Perceptions of Memory, Depressive Symptoms, and Activity Participation in Older Adults

Abstract: Background and Objectives Self-perceptions of memory problems may impact older adults’ mood as well as their activity participation, thereby negatively affecting health and well-being. We examined within-person associations among self-reported memory, depressive symptoms, as well as physical, social, and cognitive activity participation in older adults without cognitive impairment. Research Design and Methods Samples were dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Prevalence of depression was highest in the moderate participation group, but its association was lost in the fully adjusted model suggesting that depression was secondary to other factors. Hill et al showed that depressive symptoms associated with self-perceptions of memory problems contributed to lower physical and social participation (63). The low prevalence of depression in the low participation group and lack of association with participation group could be due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of depression was highest in the moderate participation group, but its association was lost in the fully adjusted model suggesting that depression was secondary to other factors. Hill et al showed that depressive symptoms associated with self-perceptions of memory problems contributed to lower physical and social participation (63). The low prevalence of depression in the low participation group and lack of association with participation group could be due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…We defined covariates based on the literature [6,8,23] and included participants' age, sex, race or ethnicity, education, living alone, functional impairment, proxy response, and place of residence. Functional impairment comprised the activity of daily living (ADL) and instrumental activity of daily living (IADL) impairments.…”
Section: Measurementsmentioning
confidence: 99%
“…Participation in meaningful activities benefits older adults' emotional and physical well-being [6,7], including those with dementia [1][2][3], providing a sense of continuity, quality of life, and self-identity [9]. Physical distancing measures during the pandemic could impede activity participation.…”
Section: Introductionmentioning
confidence: 99%